Pendidikan Damai untuk Dunia: Menelusuri Konsep Dialog Rumpun Agama Ibrahim tentang Pluralitas dalam Merespon Perbedaan - Kamarudin Zaelani; Baiq Mulianah (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2023)
Caused of the certainty of multicultural realizing, the pluralist attitudes become a necessary for consummate peacekeeping. Creating dialogue and harmony relations between human being with their differences, become our duty in any capacity for harmonious and peace life rebuild. Through of the literature study, based on using religious education study approach, this study should find any conception of peace as well as contained in the holy book of Abraham religions. For all of those become invitation for us to create the world peace. Starting from the classical texts studies, which brought the world spirit of peace and harmony in it’s diversity of race, tribe, nation, religion, flow and the economic level, this study attempt to map peace existing references that written in Abraham religion holy books. May this assay will contribute for world peace especially in peace education of religion.